2022
DOI: 10.1002/clen.202100286
|View full text |Cite
|
Sign up to set email alerts
|

Multifaceted Role of Microalgae for Municipal Wastewater Treatment: A Futuristic Outlook toward Wastewater Management

Abstract: Municipal wastewater (MWW) or urban wastewater (UWW) is generated by the domestic consumption of freshwater, which contains a huge amount of nutrients. The release of unprocessed wastewater causes eutrophication and harms aquatic life. Moreover, ingestion of polluted MWW causes a severe negative impact on human health. Microalgae are unicellular, eukaryotic photosynthetic organisms and have the capability of nutrient assimilation in the presence of light. Moreover, the produced biomass can be used for the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 113 publications
0
7
0
1
Order By: Relevance
“…Phosphorus can often be retrieved as struvite (MgNH, 4PO) or cal- it is more centralized than decentralized. To make the functioning of a nutrient-recovery facility feasible, it could be required to combine the nutrients from many different people (Fu et al, 2022).…”
Section: Nutrient Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorus can often be retrieved as struvite (MgNH, 4PO) or cal- it is more centralized than decentralized. To make the functioning of a nutrient-recovery facility feasible, it could be required to combine the nutrients from many different people (Fu et al, 2022).…”
Section: Nutrient Recoverymentioning
confidence: 99%
“…In comparison, 25% of urban residents in these countries share the same predicament. Diseases like those seen in Exhibit 1 result from inadequate sanitation services (Goswami et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Safafar et al (2015) reported that microalgae grown in industrial wastewater contain carotenoids, phenolic compounds, tocopherol, and other natural pigments which showed antioxidant activities. However, toxicity is the major concern regarding the utilization of wastewater treated algal biomass for metabolite production (Goswami et al, 2021e). Also, the integration of different physical or chemical methods in microalgae-based cultivation improved the remediation efficiency.…”
Section: Challenges and Opportunities In Microalgal Based Wastewater ...mentioning
confidence: 99%
“…While carbohydrates are saccharified into fermentable sugar and then converted into bioethanol (Goswami et al., 2022; Yao et al., 2013). Recently, the scientific community used waste compounds and wastewaters as cultivation media for the cultivation of microalgae and utilized wastewater treated biomass as feedstock for liquid biofuel production (Goswami et al., 2021; Sopandi et al., 2020) These approaches reduce the total cultivation cost of microalgae. For example, Wu et al.…”
Section: Bioenergy Generation From Microalgae‐based Wastewater Biorem...mentioning
confidence: 99%
“…Moreover, their biomass also contains pigments, such as chlorophyll, proteins, total carotenoids, β-carotene and astaxanthin, which have great applications in functional foods, pharmaceuticals, cosmetics and the feed industry [ 2 ]. The applications of microalgae are hampered by the huge production costs associated with the growth rate and biomass production, harvesting time and cellular composition of biomolecules and use of energy-intensive harvesting methods [ 3 , 4 ]. Therefore, studies on microalgae cultivation and harvesting have received great attention in recent years to reduce the cost of production and improve biomass yields [ 5 ].…”
Section: Introductionmentioning
confidence: 99%